PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN MASYARAKAT ASMAT UNTUK BERKUNJUNG BEROBAT KEMBALI MELALUI KEPUASAN PADA PUSKESMAS AGATS, DISTRIK AGATS, KABUPATEN ASMAT, PROPINSI PAPUA - Steven Langi (PROGRAM PASCA SARJANA MAGISTER MANAJEMEN INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2022)
The Agats Health Center is the first level of health service in the Agats district which is the capital of Asmat Regency and is the only health center in the area. The current phenomenon is that there are patients who make repeat visits to the Agats Health Center. The purpose of this study was to determine and analyze: 1) the effect of service quality on patient satisfaction 2) the effect of patient satisfaction on the decision to return for treatment 3) the influence of service quality on the decision to return for treatment, and 4) the influence of service quality on the decision to return for treatment. to Puskesmas Agats through satisfaction as an intervening variable. This type of research is quantitative with a survey approach. This study was conducted on patients who due to their medical history had to return for treatment to the Agats Health Center in Agats District, Asmat Regency, Papua Province. The population in this study were all patients who had visited Agats in 2021 with a research sample of 100 respondents with a history of return visits using purposive sampling technique. The results showed 1) there was a direct influence of service quality on patient satisfaction, 2) there was a direct influence on patient satisfaction with the decision to visit again for treatment, 3) there was a direct influence of service quality on the patient's decision to visit again for treatment at the Agats Health Center, Agats district, Kab. Asmat and 4) Service quality on the decision to visit for treatment again through satisfaction as a mediating/intervening variable.